Analysis Of the Influence of Profitability, Liquidity, Capital Strukture, Sales Growth and Managerial Ownership on Company Value in The Manufacturing Manufakturing Sector Enlisted in The LQ45 Index - Irma Sulastri; Nor Norisanti; Sopyan Saori (Yayasan Riset dan Pengembangan Intelektual, 2023)
The aim of this research is to analyze the impact of profitability, liquidity, capital structure, sales growth, and managerial ownership on company value in the manufacturing sector listed in the LQ45 Index. Annual financial report data of companies from 2018 to 2021 were used, and panel regression analysis was employed to examine the relationship between independent variables (profitability, liquidity, capital structure, sales growth, and managerial ownership) and the dependent variable (company value). The research findings indicate that liquidity has a significant positive influence on company value, while profitability, capital structure, and managerial ownership do not have a significant influence. Additionally, sales growth has a significant positive impact on company value. These findings provide new insights into understanding the factors influencing company value in the manufacturing sector. The theoretical implications of this research support the theories of liquidity and sales growth, which have a positive influence on company value. However, the insignificant influence of profitability and managerial ownership raises further questions that need to be explored in future research.